Cholesterol assimilation of Lactobacillus plantarum L8 and Lactobacillus pentosus S1 through in-vitro cholesterol lowering activity /Athifah Ismail, Ilyanie Hj Yaacob and Ida Muryany Md Yasin - Ismail, Athifah; Yaacob, Ilyanie; Md Yasin, Ida Muryany (UiTM Cawangan Negeri Sembilan, 2022)
Probiotics gives a new insight in treating hypercholesterolemia. Recent research found that probiotics such as Lactobacillus possess multiple health benefits including cholesterol assimilation in human body. Bile salt deconjugation and cellular cell binding were proposed as underlying mechanisms for cholesterol lowering activity. Lactobacillus plantarum L8 and Lactobacillus pentosus S1 isolated from fermented fish food known as pekasam were assessed for their ability to deconjugate bile salt such as Taurodeoxycholic acid (TDCA). To achieve this, Lactobacillus plantarum L8 and Lactobacillus pentosus S1 were tested for bile salt de-conjugation through direct plating assay on de Mann, Rogosa, Sharpe (MRS) agar supplemented with TDCA. Different stages of cell growths of these strains were also tested for their ability to reduce cholesterol in MRS broth supplemented with cholesterol. Bacterial growth was also observed to identify whether incorporation of cholesterol in MRS broth would affect the growth pattern of L. plantarum L8 and L. pentosus S1 and their correlation with cholesterol reduction. The result showed that both L. plantarum L8 and L, pentosus S1 did not deconjugate bile salt on selective agar. However, only the growing, resting, and dead cells of L. plantarum L8 were able to assimilate cholesterol by 33%, 8% and 1%, respectively, while those of L. pentosus S1 did not show any activity which might be due to species specificity. Besides, L. plantarum L8 has a faster doubling time and a higher growth rate as compared to L. pentosus S1. This explains the cholesterol removal of L. plantarum L8 being higher than L. pentosus S1. Besides, after 18 h of incubation, L. plantarum L8 supplemented with cholesterol had a maintained growth up to 24 h as compared to its control (absence of cholesterol). In conclusion. L. plantarum L8 has the potential to act as cholesterol lowering probiotics.